MINERALOGY OF TAGISH LAKE: AN UNGROUPED TYPE 2 CARBONACEOUS CHONDRITE - Zolensky M.E.; Nakamura K.; Gounelle M.; Mikouchi T.; Kasama T.; Tachikawa O.; Tonui E. (My University, 2002)
In this paper we describe the recovery, handling and preliminary mineralogical investigation of the Tagish Lake meteorite. Tagish Lake is a type 2 carbonaceous chondrite which bears similarities to CI1 and CM chondrite groups, but is distinct from both. Abundant phyllosilicates as well as chondrules (however sparse) and common olivine grains in the matrix preclude any other classification. The bulk density of Tagish Lake (1.67 g/cc) is far lower than CI or CM chondrites (2.2-2.3 and 2.6-2.9 g/cc, respectively), or any other meteorite for that matter. We have identified two lithologies: a dominant carbonate-poor lithology and a less-abundant carbonate-rich lithology. The meteorite is a breccia at all scales. We have noted similarities between Tagish Lake and some clasts within the enigmatic meteorite Kaidun; possibly there are genetic relationships here worth exploring. In the paper we describe a clast of CM1 material within Tagish Lake which is very similar to a major lithology in Kaidun.